KEBIJAKAN PEMANFAATAN RUANG TERBUKA HIJAU KABUPATEN DAN PERKOTAAN: STUDI KASUS PROVINSI BANTEN - Epi Syahadat; Sylviani Sylviani (Jurnal Analisis Kebijakan Kehutanan, 2016)
Green open space (GOS) is a space that is dominated by the natural environment, both outside as well as inside the city, in the form of a garden, courtyard, city recreation areas and green belt. The provision of green open space is a challenge in spatial planning, especially in terms of land acquisition. This study aims to assess regulatory policies on development and utilization of GOS issued by the relevant technical ministries. The analytical method used in this study was qualitatif descriptive, based on desk studiy and assessments from the field in the Banten Province. The result of the study indicated that regulatory policy was done through the process of zoning regulation with the intent that the guideline of land use in line with spatial plans. Funding source of this GOS came from Regional Budget Planning and other resources where the activities were monitored by the respective Governor in coordination with Regent/ Mayor.  It needs a strong commitment between Central Government and Local Goverment in developing GOS. Control and utilization of urban space were organized by the governmentand involving community's participation